Acceptance Testing of Unit A4 of HE “Đerdap 1” Excitation System - Joksimović, Dušan; Ćirić, Zoran; Klasnić, Ilija; Arnautović, Dušan; Bogdanović, Slobodan; Milojčić, Nemanja (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
Acceptance test results of the HE “Djerdap 1” unit A4 excitation system are presented. The excitation system under study had been delivered and commissioned during unit A4 refurbishment works in 2013, while acceptance tests were conducted during 2014. The test purpose was to prove the contracted performances of the delivered excitation system. The test and measuring equipment used were with certified accuracy.